Analyses of SLC13A5-epilepsy patients reveal perturbations of TCA cycle - Bainbridge, Matthew N.; Cooney, Erin; Miller, Marcus; Kennedy, Adam D.; Wulff, Jacob E.; Donti, Taraka; Jhangiani, Shalini N.; Gibbs, Richard A.; Elsea, Sarah H.; Porter, Brenda E.; Graham, Brett H. (Molecular genetics and metabolism, 2017)
To interrogate the metabolic profile of five subjects from three families with rare, nonsense and missense mutations in SLC13A5 and Early Infantile Epileptic Encephalopathies (EIEE) characterized by severe, neonatal onset seizures, psychomotor retardation and global developmental delay. Mass spectrometry of plasma, CSF and urine was used to identify consistently dysregulated analytes in our subjects. Distinctive elevations of citrate and dysregulation of citric acid cycle intermediates, supporting the hypothesis that loss of SLC13A5 function alters tricarboxylic acid cycle (TCA) metabolism and may disrupt metabolic compartmentation in the brain. Our results indicate that analysis of plasma citrate and other TCA analytes in SLC13A5 deficient patients define a diagnostic metabolic signature that can aid in diagnosing children with this disease. •SCL13A5 deficiency shows disrupted citrate in plasma that is readily detectable by mass-spectrometry.•Multiple metabolites of the citric acid cycle and downstream analytes, including neurotransmitters, are disrupted in the CSF.•Mass-spectrometry of CSF can be used to identify SLC13A5 deficiency and inform whole exome sequencing results.